Analisis Wacana: Partisipasi Perempuan dalam Politik di Indonesia Tahun 2018 - 2019 - Herdin Arie Saputra; Dyah Mutiarin; Achmad Nurmandi (UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
In Indonesia, the role of women in the political world is not statistically arguably contributing massively, due to several resistance that must be considered. Women's participation in politics should be balanced with men who are massively dominant in political positions. Because the rights between men and women's rights have the same recognition in state life in Indonesia based on the 1945 Constitution. The Islamic view is to always pay attention to the concepts of justice, wholeness, harmony, the balance of fellow human beings with nature. The purpose of this study is to determine women's participation in politics in Indonesia and to be a reference for women to participate in politics (executive and legislative). This type of research used in this research is qualitative research. The analysis used from this paper is descriptive analyzes. Analyzes were performed using the Nvivo 12 plus software. The results of the study are the lack of women's education on politics, regeneration of political parties, issues of permission from spouses, financial capital, descendants of political figures, patriarchal beliefs and culture that are still thick. This is an obstacle for women in participating in politics.